PENGARUH PENGALAMAN AUDITOR, PENERAPAN KODE ETIK DAN TEKANAN ANGGARAN WAKTU TERHADAP KUALITAS AUDIT (Survey Pada Auditor Di Kantor Inspektorat: Kota Palu, Kabupaten Sigi Dan Kabupaten Donggala) - Alif, Nur; Jamaluddin, Jamaluddin; Laupe, Supriadi (Jurnal Akun Nabelo: Jurnal Akuntansi Netral, Akuntabel, Objektif, 2020)
This study aims to determine and analyze the effect of Auditor Experience, Application of Code of Ethics And Time Budget Pressure to audit quality at Inspectorate Offices: Palu City, Sigi Regency and Donggala Regency. This type of research is survey research, using sampling technique of cencus method. The data were collected with distributing questionnaries to 45 auditors who working at the Inspectorate Office:Palu City, Sigi Regency and Donggala Regency. Primary data obtained from the responses of respondens through the spread of questionnaries and observation. The analysis tool used is multiple linear regression analysis. The results of this study shows that partialy affected the auditors experience has a positive and significant effect to audit quality. The application of code of ethics has a positive and significant effect to audit quality and time budget has a positive and significant effect to audit quality